FRI0331 HISTORY OF SILICA DUST EXPOSURES AND ASSOCIATION WITH CHEST HRCT AND CLINICAL CHARACTERISTICS IN SYSTEMIC SCLEROSIS. (June 2019) - Ballerie, Alice; Cavalin, Catherine; Lederlin, Mathieu; Nicolas, Amélie; Garlantezec, Ronan; Jouneau, Stéphane; Cazalets, Claire; Belhomme, Nicolas; Rosental, Paul-Andre; Jégo, Patrick; Alain, LESCOAT
Abstract : Background: The association of a history of silica exposure with precise chest high-resolution computed tomography (HRCT) features are still to be determined in SSc patients fulfilling the 2013 EULAR/ACR classification criteria. A recent study highlighted that mediastinal lymph nodes were associated with worse prognosis in all-cause interstitial lung diseases (ILD) (1). Nonetheless, the links between mediastinal lymphadenopathies (LA) and silica exposure in SSc patients have never been studied to date. Objectives: The aim of this study was to assess the association of exposures to inorganic particles on the whole life course, with the HRCT characteristics in an unselected population of SSc patients. Methods: A specific questionnaire based on a multidisciplinary approach (social sciences, epidemiology, occupational health and medicine) was used to assess occupational and non-occupational exposures to inorganic particles, with a specific interest on silica exposures in 100 SSc patients fulfilling the 2013 EULAR/ACR classification criteria. Clinical characteristics and chest HRCT at diagnosis were evaluated to assess the association of dust exposure with disease characteristics. The most recent chest HRCT was also evaluated and compared to HRCT at diagnosis to assess pulmonary evolution. All HRCT were evaluated by 3 experts, blinded for the results form dust exposure questionnaire. Results: Men had significantly higher global and occupational dust-exposure scores than women. Sixty-five percent of men with SSc (n=17) had an occupational exposure to silica. Thirty-five percent of patients had thoracic LA and 12% an association of mediastinal and hilar LA. Male gender, history of tobacco use, dcSSc, positivity for ATA, thoracic LA and pneumoconiosis were significantly associated with occupational exposure to silica (p<0.05 for all). The presence of mediastinal and hilar LA was also associated with occupational exposure to silica (p=0.0001, OR=13.45, 95%CI=3.46-52.27). After stratification on gender, higher occupational dust-exposure score in men remained associated with mediastinal and hilar LA (p=0.046, OR=6.5, 95%CI=1.09-38.63). Mediastinal and hilar LA were also significantly associated with a more severe evolution of pulmonary involvement in SSc when considering extensive ILD at diagnosis, the use of immunosuppressive drugs, a fibrotic evolution with change of SSc-ILD pattern in the course of the disease, and an increase of pathological parenchyma extent above 10% since diagnosis. Conclusion: By using a dedicated highly detailed questionnaire, this study underscores the high prevalence of silica exposure in SSc patients, especially in men. Mediastinal and hilar LA, considered as a bad prognostic factor in ILD, were frequent and associated with silica exposure. References: [1] Adegunsoye A, et al. Prognosticating Outcomes in Interstitial Lung Disease by Mediastinal Lymph Node Assessment: An Observational Cohort Study with Independent Validation. Am J Respir Crit Care Med. 2018Sep14. Disclosure of Interests: None declared